Common Envelope Evolution on a Moving Mesh - Prust, Logan J. (Proceedings of the Wisconsin Space Conference, 2020)
The common envelope phase in binary star systems is simulated using the 3-D moving-mesh hydrodynamic code MANGA. Improvements to MANGA to improve accuracy and computation time are discussed. Two open questions in the physics of common envelope evolution are investigated. The effects of tidal forces present before the onset of a common envelope phase are explored by comparing simulations in which the giant star is initialized with varying degrees of rotation. The role of hydrogen recombination energy is investigated by using two different equations of state, only one of which includes the effects of recombination. Rotation is shown to increase the final binary separation, while recombination energy decreases the separation. Future improvements to MANGA to capture additional physics present in common envelopes are discussed.